Student Edited Law Journals: Strengthening the Creativity of Law Students in a Challenging Era (Journal of Creativity Student, 2022)
Harvard Law School (HLS) is one of the world's leading law schools. HLS graduates have had a significant impact on the development of international law. The HLS dialectics and academic climate grew through various student discussion forums, one of which was the student journal forum. At HLS, student edited journals are one of the routine activities of students at all levels, both undergraduate, postgraduate, and doctoral programs. Many student edited journals at HLS are included in the category of reputable international journals (either Scopus or Web of Science). The governance of student journals at HLS can be traced transparently on the HLS official website and it is very possible to be adopted and modified in the governance of law student journals at the State University of Semarang. Nevertheless, there is a big challenge to be faced, namely the quality of human resources. So that this service program aims to develop human resources in the management of student journals by adopting and modifying the management style of student edited journals at Harvard Law School. This program is in collaboration with UKM Lex Scientia, a unit that focuses on research and publication activities for law students. The output of this program is expected to create a proposed model for the management of an ideal law student journal within the State University of Semarang. In addition, through this program, it is hoped that there will be an increase in the quality of human resources in the management of law student journals. This program will have direct implications for improving the quality and quantity of student publications and will directly affect the achievement of the University's IKU and the level of UNNES ranking on an international scale.